2011
DOI: 10.1111/j.1399-3038.2010.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune neutropenia in children: analysis of 116 cases

Abstract: Diagnosis of autoimmune neutropenia (AIN) in infants is important, because it allows the exclusion of more severe forms of neutropenia that have an increased risk for leukemia. AIN is characterized by chronic neutropenia, which spontaneously resolves within several months to a few years, and mild infections. Diagnosis is confirmed by the presence of antibodies directed against neutrophil antigens. The human neutrophil antigen (HNA) system is a polymorphic system, which includes five antigen groups with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 13 publications
6
26
2
1
Order By: Relevance
“…this may be due to a stricter infection definition applied in the present study. 3,5 skin and subcutaneous tissues were the most common sites regardless of the type of neutropenia, and accounted for greater than half the cases of infections. this is in agreement with the fact that skin/subcutaneous lesions are events often leading to diagnosis because they tend to recur and to be difficult to eradicate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…this may be due to a stricter infection definition applied in the present study. 3,5 skin and subcutaneous tissues were the most common sites regardless of the type of neutropenia, and accounted for greater than half the cases of infections. this is in agreement with the fact that skin/subcutaneous lesions are events often leading to diagnosis because they tend to recur and to be difficult to eradicate.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although pathogenesis of K. kingae invasive infections remains unclear, there is evidence that K. kingae first colonizes the oropharynx before penetrating the bloodstream and invading distant organs. 5 previous studies suggested that respiratory carriage of K. kingae is a prerequisite for distant infection of joint and bone. [6][7][8] the oropharyngeal carriage of K. kingae does not necessary imply the subsequent development of an invasive infection, and the probability for asymptomatic children carrying K. kingae to develop an osteoarticular infection is lower than 1%.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The historical incidence is reported to be 1 out of 100,000 children under 10 years of age [Lyall et al 1992] but, due to the benign course of the disease, there is clear evidence of underreporting, highlighted by frequent fortuitous findings (8-27% of all cases) [Bux et al 1998;Audrain et al 2011]. In our experience, diagnosis as consequence of a blood count planned for other reasons (i.e.…”
Section: Introductionmentioning
confidence: 67%
“…The detection of these antibodies is technically difficult; thus they are not always evaluated in clinical practise. 19,20 The etiology of neutropenia is most often autoimmune or idiopathic. 4,6,10 CIN was found to be caused by one of these etiologies in a similar proportion of our patients (34.0% to 68.9%) compared with previously studied cohorts.…”
Section: Discussionmentioning
confidence: 99%